Development and Implementation of the Convolution Method for Photon Dose Calculation in Radiation Therapy - Keyvan Jabbari; Mohamad Bagher Tavakoli; Sayed Mojtaba Hosseini (مجله دانشکده پزشکی اصفهان, 2012)
Background: One of the most widely used methods in cancer treatment is radiation therapy. In radiation therapy, the goal is to deliver maximum dose to the cancerous tissue and the least amount to adjacent normal tissue. Therefore, it is important to calculate radiation doses received by different points of body. These calculations are performed by treatment planning systems. The aim of this project was to develop and implement the convolution algorithm in the form of a code. The accuracy of doses calculated by the code was then compared with experimental values. Methods: Full scatter convolution method was used in this project. Considering a phantom with dimensions of 11.5 × 11.5 × 11.25 cm3 and field sizes of 3 × 3, 5 × 5, and 10 × 10 cm2 on its surface, the code was written by MATLAB program. Incident photon energy was considered as 6 MeV. Finally, percentage depth dose values were compared with experimental values. Findings: The mean percent difference values were 1.527%, 1.51%, and 3.00% for field sizes of 3 × 3, 5 × 5, and 10×10 cm2, respectively. Conclusion: Percentage differences between the doses calculated by the code and experimental values were less than 5% for all three field sizes. According to the recommendations of Task Group 53 of the Radiation Therapy Committee of the American Association of Physicists in Medicine, the values were in the acceptable range. Keywords: Radiotherapy planning, Radiation therapy, Photons, Convolution algorithm